IMPACT OF COVID-19 PANDEMIC ON THE LOCAL TAX - Jouzar Farouq Ishak (International Conference on Social and Islamic Studies, 2021)
The purpose of government is to proper the community by using fund from the people,one of which is local tax. Covid-19 not only affects health, but also affects local taxconditions. The study was conducted with the aim to analyze whether there aredifference local tax before and after covid-19 pandemic. The sample used in this study isthe period of 2019 and 2020 in the report on budget realization. There are 34 provincialgovernment in Indonesia as sample. Data were analyzed using IBM SPSS 23.0.Hypothesis testing is performed using paired sample t-test. The result of this studyindicates that there are difference in local tax at the time before and after Covid-19pandemic. The current pandemic situation has a major impact on regional economy,including in the taxation sector. The impact of the Covid-19 pandemic with the declinein local tax revenues was due to the people being affected by being laid off and partiallockdown. How long this pandemic lasts and how much impact it will have on economicactivity will determine the future of the regional tax sector in Indonesia.